Frequency and Severity of Drooling in Children with Cerebral Palsy– A Cross-Sectional Study - Happy, Romana Akter; Debnath, Bithi; Rashid, Muhammed Anisur; Hussain, Sharmin; Shahed, Md Humayun; Rahman, SK Masiur; Shira, Mushtab (Journal of Rangpur Medical College, 2026)
Background: Drooling is a common problem in children with cerebral palsy (CP), which has both physical and psychological impacts. So, this problem should be addressed among the CP patients. Objective: The aim of this study was to find out the frequency and severity of drooling in children with Cerebral palsy. Methods: This was a cross-sectional study conducted in the Pediatric Neurology outpatient department of the National Institute of Neurosciences and Hospital (NINS), Dhaka, from January to December 2022. A total of 100 children aged 3–14 years with a primary diagnosis of cerebral palsy who had drooling were included. The severity and frequency of drooling were assessed by Thomas Stonell and the Greenberg drooling rating scale. This Scale was used to measure the drooling severity and frequency. Data were collected via a structured questionnaire and analyzed using SPSS (version 25), with p<0.05 considered statistically significant. Ethical approval was obtained, and informed consent was secured from parents/caregivers. Results: Among the 100 participants, 54% were male and 46% were female, and about half of them were under five years of age. Spastic quadriplegia was the most prevalent CP type (45%), followed by spastic hemiplegia (30%), diplegia (19%), and dyskinetic CP (6%). Constant (42.2%) and frequent (37.8%) drooling were observed predominantly in children with spastic quadriplegia (p=0.007). In terms of severity, severe drooling was most common (74.2%), followed by profuse (50%) and moderate drooling (34.7%) in quadriplegic CP children (p=0.001), then diplegic and hemiplegic children. Conclusion: This study highlighted that the drooling frequency and severity both had a significant association with the types of CP. J Rang Med Col.2026 Mar;11(1): 57-62